Respuesta :

The equation y = 2x + 3 is a linear equation, and the equivalent equation of y = 2x + 3 is y - 3 - 2x = 0

How to determine the equal equation?

The equation is given as:

y = 2x + 3

Subtract 3 from both sides

y - 3 = 2x

Subtract 2x from both sides

y - 3 - 2x = 0

The above means that the equation y - 3 - 2x = 0 is equal to the equation  y = 2x + 3

Hence, the equivalent equation of y = 2x + 3 is y - 3 - 2x = 0

Read more about equivalent equations at:

https://brainly.com/question/2972832

#SPJ1